Would you promote/tenure this candidate? Selecting external reviewers - Nancy P. Kropf (Academic Chairpersons Conference Proceedings, 2018)
One of the most important junctures in a faculty member’s professional life is the review for promotion and/or tenure. This presentation highlights the importance of strategic decision-making about external reviewers as part of P & T. Methods that chairs can use to mentor faculty in this process are presented.
Keywords: promotion; tenure; external reviews; faculty review; mentoring